MODERNIZING CUSTOMS FOR CITES ENFORCEMENT: ENHANCING TRANSPARENCY AND CROSS-BORDER COOPERATION IN MALAYSIA: ENHANCING TRANSPARENCY AND CROSS-BORDER COOPERATION IN MALAYSIA - MOHD HAIRUL MOHD SALLEH (JURNAL PERSPEKTIF BEA DAN CUKAI, 2025)
This review examines the strategic role of the Royal Malaysian Customs Department (RMCD) in enhancing transparency and cross-border cooperation for the enforcement of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Given Malaysia’s position as a critical transit hub for wildlife trafficking, this study addresses key challenges such as fragmented data systems, weak interagency coordination, and limited species identification capacity. Using a qualitative, narrative-based approach, the review analyzes literature, regional initiatives (e.g., ASEAN-WEN), and customs modernization tools, including ePermits, non-intrusive inspection, and AI-based risk profiling. The results reveal progress in digitization and regional cooperation, yet underscore persistent gaps in real-time data interoperability, legal harmonization, and officer training. Discussion highlights the need for standardized procedures, cross-border intelligence exchange, and policy reform to align enforcement practices with international biodiversity goals. Conclusively, the study proposes a multi-layered strategy—integrating technological innovation, regulatory alignment, and regional capacity building—to enhance CITES enforcement and position RMCD as a regional leader in biodiversity protection.